Looking for invisible clues - Wright, Lee-Ann (Pearson London, 2012)
This mystery-themed book sparks curiosity and problem-solving skills in young readers. Through a series of puzzles and riddles, children are challenged to uncover hidden clues and solve the mystery, fostering critical thinking and deductive reasoning.